Incorporating Clinical Imaging into the Delivery of Microbeam Radiation Therapy - Jason Paino; Micah Barnes; Elette Engels; Jeremy Davis; Susanna Guatelli; Michael de Veer; Chris Hall; Daniel Häusermann; Moeava Tehei; Stéphanie Corde; Anatoly Rosenfeld; Michael Lerch (Applied Sciences, 2021)
Synchrotron microbeam radiation therapy is a promising pre-clinical radiation treatment modality; however, it comes with many technical challenges. This study describes the image guidance protocol used for Australia’s first long-term pre-clinical MRT treatment of rats bearing 9L gliosarcoma tumours. The protocol utilises existing infrastructure available at the Australian Synchrotron and the adjoining Monash Biomedical Imaging facility. The protocol is designed and optimised to treat small animals utilising high-resolution clinical CT for patient specific tumour identification, coupled with conventional radiography, using the recently developed SyncMRT program for image guidance. Dosimetry performed in small animal phantoms shows patient dose is comparable to standard clinical doses, with a CT associated dose of less than <semantics>1.39</semantics><semantics>c</semantics>Gy and a planar radiograh dose of less than <semantics>0.03</semantics><semantics>c</semantics>Gy. Experimental validation of alignment accuracy with radiographic film demonstrates end to end accuracy of less than <semantics>±0.34</semantics><semantics>m</semantics><semantics>m</semantics> in anatomical phantoms. Histological analysis of tumour-bearing rats treated with microbeam radiation therapy verifies that tumours are targeted well within applied treatment margins. To date, this technique has been used to treat 35 tumour-bearing rats.